Biodiversity within phytoplankton-associated microbiomes regulates host physiology, host community ecology, and nutrient cycling - Jonathan R. Dickey; Nikki M. Mercer; Mirte C. M. Kuijpers; Ruben Props; Sara L. Jackrel (mSystems)
ABSTRACT Biological diversity is declining across the tree of life, including among prokaryotes. With the increasing awareness of host-associated microbes as potential regulators of eukaryotic host physiology, behavior, and ecology, it is important to understand the implications of declining diversity within host microbiomes on host fitness, ecology, and ecosystem function. We used phytoplankton and their associated environmental microbiomes as model systems to test the independent and interactive effects of declining microbiome diversity with and without other stressors often caused by human activity—elevated temperature and altered nutrient availability. We found effects of low microbiome diversity on host physiology, phytoplankton community dynamics, and nutrient cycling. Low microbiome diversity caused greater host cellular stress, as indicated by elevated δ13C and δ15N. Microbiome diversity also significantly affected host cell morphological metrics, likely as a consequence of this effect on cell stress. Despite causing greater host cellular stress, the effects of low microbiome diversity on host community ecology included elevated phytoplankton community diversity and biomass. The diversity of these host-associated microbes also had cascading implications on ecosystem nutrient cycling, where lower microbiome diversity caused a depletion of total dissolved N and P in the environment. The magnitude of these effects, caused by microbiome diversity, was greatest among nutrient-depleted environments and at elevated temperatures. Our results emphasize the widespread implications of declining host-associated microbial diversity from host cellular physiology to ecosystem nutrient cycling. These demonstrated effects of declining microbiome diversity are likely to be amplified in ecosystems experiencing multiple stressors caused by anthropogenic activities.IMPORTANCEAs evidence is emerging of the key roles that host-associated microbiomes often play in regulating the physiology, fitness, and ecology of their eukaryotic hosts, human activities are causing declines in biological diversity, including within the microbial world. Here, we use a multifactorial manipulative experiment to test the effects of declining diversity within host microbiomes both alone and in tandem with the effects of emerging global changes, including climate warming and shifts in nutrient bioavailability, which are inflicting increasing abiotic stress on host organisms. Using single-celled eukaryotic phytoplankton that harbor an external microbiome as a model system, we demonstrate that diversity within host-associated microbiomes impacts multiple tiers of biological organization, including host physiology, the host population and community ecology, and ecosystem nutrient cycling. Notably, these microbiome diversity-driven effects became magnified in abiotically stressful environments, suggesting that the importance of microbiome diversity may have increased over time during the Anthropocene.